Increasing Tourist Revisit Intention in Garut Tourist Attractions: The Role of Destination Image and Tourist Satisfaction - Amalia, Rena; Wibisono, Nono; Elliott-White, Martin (Politeknik Negeri Bandung, 2023)
Garut has plenty of attractive tourist destinations to visit, but there are several complaints about tourist dissatisfaction with the government regarding the poor quality of accommodation and safety at the attractions. This led to their reconsideration to not revisiting Garut again and prefer to choose other regencies for vacation. This study examines the importance of destination image dimensions: destination attractiveness, accommodation, as well as safety and security in Garut tourism towards tourist satisfaction to increase revisit intention. Data was obtained through online questionnaires with the Likert scale from 410 respondents who had visited Garut tourism. This study employs SEM-PLS, and the results show that destination attractiveness, accommodation, and safety & security, have a role in building revisit intention. The three elements of destination image have a positively significant role in increasing satisfaction, and tourist satisfaction also positively significantly affects revisit intention. The outcome of this study can be a new insight into literature regarding destination image, tourist satisfaction, and revisit intention, as well as offering a solution for government and tourism managers in Garut in developing tourist destinations. As attractive tourist destinations with a good quality of accommodation, completed by safety and security, will increase the satisfaction and revisit intention.